2021
DOI: 10.3390/su13094941
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Reforms and Their Impact on Economic Growth and Investment in Developing Countries

Abstract: It is widely accepted that the economic and social system may be more efficient by reforming institutions. Institutional reforms are attempts to change the rules affecting human interactions and these reforms are fundamental for development and economic prosperity. The reforms can be divided into two categories; political and economic institutional reforms. It is need of the hour to determine the category of reform that is more suitable for developing countries. Moreover, a vast literature describes the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
(84 reference statements)
4
14
0
Order By: Relevance
“…Any effort to improve the INQ will promote the long-run economic performance of the economy. The outcome is similar to the findings by Alexiou et al (2014), Nawaz et al (2014), Nguyen et al (2018), Salman et al (2019), Marija (2020), Sule (2020) and Zhao et al (2021) who reported important contribution of INQ to EG. It implies that policymakers should strive to improve the country's institutions and their service quality to sustain EG.…”
Section: Ardl (1 1 1 2) Long-run Outputsupporting
confidence: 90%
See 2 more Smart Citations
“…Any effort to improve the INQ will promote the long-run economic performance of the economy. The outcome is similar to the findings by Alexiou et al (2014), Nawaz et al (2014), Nguyen et al (2018), Salman et al (2019), Marija (2020), Sule (2020) and Zhao et al (2021) who reported important contribution of INQ to EG. It implies that policymakers should strive to improve the country's institutions and their service quality to sustain EG.…”
Section: Ardl (1 1 1 2) Long-run Outputsupporting
confidence: 90%
“…(2018), Salman et al. (2019), Marija (2020), Sule (2020) and Zhao et al. (2021) who reported important contribution of INQ to EG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abubakar (2020) utilized time-series data over the period 1979–2018, applied the OLS method, scrutinized the consequence of “INQ on EG” in Nigeria, and conveyed that INQ stimulated economic progress. Zhao et al. (2021) observed the impact of formal reforms on developing countries’ investment and economic expansion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is interesting to note that institutional improvements are required whether the economy is growing or in a state of crisis. If a country is in the midst of a crisis, reforms are an important aspect of crisis management (Zhao et al, 2021). But the sequencing of reforms matters a lot.…”
Section: Discussionmentioning
confidence: 99%